Path of the Lncubus - Chambers, Andy (2013)
"The eternal city of Commorragh has been cast into turmoil by the Dysjunction, a cataclysmic disturbance in the very fabric of its existence. As the streets are inundated with horrors from beyond the veil the supreme overlord, Asdrubael Vect, battles to keep his enemies in check and maintain his stranglehold over the riven city. Kabal turns upon kabal, archon against archon as the fires of hell are unleashed. Redemption for Commorragh rests in the hands of a disgraced incubus warrior wrongly accused of triggering the Dysjunction itself. His efforts to reclaim his lost honour could save the city or damn it forever -- assuming it can survive the daemonic invasion and the archons' deadly battles for supremacy."--Page 4 of cover